ASUHAN KEBIDANAN PERSALINAN NORMAL DI RUMAH BERSALIN BUNDA PUJA TEMBILAHAN TAHUN 2019 - Nuriyah Sinta; Ernawati (Jurnal Kesehatan Husada Gemilang, 2021)
Normal delivery according to the World Health Organization (WHO) is delivery with the presentation of the fetus behind the head that takes place spontaneously with normal limits of 37-42 weeks. Maternal mortality rate (MMR) in Indonesia In 2015 was 305 per 100,000 live births. Indragiri Hilir Health Office in 2019 the number of maternal deaths in Indragiri Hilir district amount to 9 people from the number of live births or during pregnancy until the postpartum period. Able to provide midwifery care to Mrs. “R” G1P0A0H0 with normal childbirth in Bunda Puja Maternity Home with SOAP documentation and able to distinguish between theory and practice. The method used is descriptive with non probability sampling techniques with a purposive sampling approach. From the results of care for Mrs. "R" G1P0A0H0, gestational age 38 weeks 5 days in the first and second stages with a time of 2 hours 30 minutes, the supporting examination showed a gap between theory and practice, the third stage when the early initiation of breastfeeding was successfully carried out but only 15 minutes and there was a gap between theory and practice, The baby’s weight comes in the first six hours there is a gap between the theory and practice of giving immunizing Hb0, and SHK. It is expected that health workers can improve the quality of health services, especially in providing midwifery care to maternity mothers and follow APN training in order to update knowledge in accordance with their development.